Odpowiedź :
Rozwiązanie zadania:
[tex]a) \ \frac{1}{2} x-4=x-6 \ \ \ \ \ \ \ \ / * 2[/tex]
[tex]x - 8 = 2x - 12[/tex]
[tex]2x - x = -8+12[/tex]
[tex]x = 4[/tex]
[tex]b) \ x-5=\frac{1}{3} x+1 \ \ \ \ \ \ \ /*3[/tex]
[tex]3x-15=x+3[/tex]
[tex]3x-x=3+15[/tex]
[tex]2x = 18 \ \ \ \ \ \ \ /:2[/tex]
[tex]x = 9[/tex]
[tex]c) \ \frac{x}{4} -\frac{1}{4} = 2 \ \ \ \ \ \ /*4[/tex]
[tex]x-1=8[/tex]
[tex]x = 9[/tex]
[tex]d) \ \frac{x}{5} -3=x+\frac{1}{5} \ \ \ \ \ \ \ \ /*5[/tex]
[tex]x-15=5x+1[/tex]
[tex]5x-x=-15-1[/tex]
[tex]4x=-16 \ \ \ \ \ \ \ /:4[/tex]
[tex]x=-4[/tex]
[tex]e) \ \frac{5}{6} (x-1)=4 \ \ \ \ \ /*6[/tex]
[tex]5(x-1)=24[/tex]
[tex]5x-5=24[/tex]
[tex]5x = 29 \ \ \ \ \ \ /:5[/tex]
[tex]x=\frac{29}{5} = 5\frac{4}{5}[/tex]
[tex]f) \ -\frac{1}{2} (-x-6)=-x \ \ \ \ \ \ \ /*2[/tex]
[tex]-(-x-6)=-x[/tex]
[tex]x+6=-x[/tex]
[tex]2x=-6 \ \ \ \ \ \ \ \ /:2[/tex]
[tex]x=-3[/tex]
Odpowiedź:
a) x = 4
b) x = 9
c) x = 9
d) x = -4
e) x = 5,8
f) x = -2
Szczegółowe wyjaśnienie:
a) 0,5x - x = -6 + 4
-0,5x = -2
x = 4
b) 3x - 15 = x + 3
2x = 18
x = 9
c) x - 1 = 8
x = 8 + 1
x = 9
d) x - 15 = 5x + 1
x - 5x = 1 + 15
-4x = 16
x = -4
e) 5/6x - 5/6 = 4 (5/6 = pięć szóstych)
5x - 5 = 24
5x = 24 + 5
5x = 29
x = 5,8
f) 0,5x + 3 = -x
x + 6 = -2x
x + 2x = -6
3x = -6
x = -2